Acute Hemorrhagic-Onset Atypical Meningioma: A Report of Two Cases with Emergent Resection Achieving Mid-Term Tumor Control and Neurological Preservation - Tsuchiya, Takahiro; Shinya, Yuki; Inoue, Tomohiro; Ohara, Kenta; Morikawa, Teppei; Tanishima, Takeo; Tamura, Akira; Saito, Isamu; Ono, Hideaki (Asian Journal of Neurosurgery, 2024)
The majority of meningiomas are slow-growing benign tumors that can potentially be highly vascularized; however, acute hemorrhagic onset is rare. Herein, we describe two patients who presented with disturbance of consciousness and severe hemiplegia due to spontaneous hemorrhage from a falx atypical meningioma. A 49-year-old female presenting with a sudden disturbance of consciousness and severe left hemiplegia was found to have a falx meningioma and acute hemorrhage. Emergent resection achieved neurological relief and tumor control. A 60-year-old female with aphasia and severe right hemiplegia also had falx meningioma and hematoma, and successfully treated by emergent resection. Tumor was diagnosed as atypical meningioma in both cases. Both patients achieved mid-term tumor control for 4 and 7 years. Both patients were treated successfully with emergent surgical resection, and neurological relief and mid-term tumor control (7 and 4 years, respectively) were achieved. Given this success, immediate surgical resection with hematoma evacuation should be considered an acceptable therapeutic option for acute hemorrhagic atypical meningioma.
Keywords: atypical meningioma; hemorrhagic onset; resection; tumor control